Dampak Pandemi Covid-19 Terhadap Kegiatan Belajar Mengajar Di MI/SD (Studi KBM Berbasis Daring Bagi Guru dan Siswa) - Ainur Risalah; W Ibad; L Maghfiroh; M I Azza; S A Cahyani; Z A Ulfayati (JIEES : Journal of Islamic Education at Elementary School, 2020)
Education is very important to improve the quality of life of every person. In education we are taught many things ranging from the value of life, general knowledge, morals and a variety of other sciences. In education there is the term KBM (Teaching and Learning Activities) where there are students and teachers who are connected in the delivery of knowledge or information as we know it happens in schools. But lately a virus outbreak has arisen that is troubling the world's population. Covid-19 virus or coronavirus is a disease originating from China and experts state that strong indications that the cause of SARS, this virus causes respiratory infections that spread through respiratory secretions, then the nose in the walls of the upper respiratory tract, some facts mention that this coronavirus raises many deaths. In this case, the government rules out to stop any activities and switch to stay and do activities at home. All institutions are closed as well as the world of education. So it switches to studying at home using an online system. For this reason, this study was conducted with the aim of knowing the effect of the co-19 pandemic in teaching and learning activities, especially the MI/SD level. This research was conducted at the home of each writer precisely in Bojonegoro, Lamongan, Sidoarjo and Surabaya by observing younger siblings who were still in elementary/MI school on March 17 to 18 April 2020. This study used a qualitative methodology. The data collection techniques using interviews, observation and documentation. Based on the results of the study note that social media is a science in learning activities during the co-19 pandemic, but in addition to being a bridge of knowledge, social media also has a negative influence on elementary school age children. Therefore the role of parents is very important in supervising children during the online learning process because elementary school age children/MIs are still at an unstable level and very much need guidance in carrying out online-based learning so that nothing unexpected happens.